2002
DOI: 10.1140/epjb/e20020109
|View full text |Cite
|
Sign up to set email alerts
|

Slow relaxation experiments in disordered charge and spin density waves: collective dynamics of randomly distributed solitons

Abstract: We show that the dynamics of disordered charge density waves (CDWs) and spin density waves (SDWs) is a collective phenomenon. The very low temperature specific heat relaxation experiments are characterized by: (i) "interrupted" ageing (meaning that there is a maximal relaxation time); and (ii) a broad power-law spectrum of relaxation times which is the signature of a collective phenomenon. We propose a random energy model that can reproduce these two observations and from which it is possible to obtain an esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Larkin [4] and Ovchinnikov [5] have shown that a single strong pinning impurity leads to a bound state of an electronlike soliton and a hole-like antisoliton. This results in a potential V (ϕ(y i )) with multiple minima [6], leading to slow relaxation in agreement with the very low temperature heat relaxation experiments [5].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Larkin [4] and Ovchinnikov [5] have shown that a single strong pinning impurity leads to a bound state of an electronlike soliton and a hole-like antisoliton. This results in a potential V (ϕ(y i )) with multiple minima [6], leading to slow relaxation in agreement with the very low temperature heat relaxation experiments [5].…”
supporting
confidence: 82%
“…This allows a systematic study of the equilibrium energy relaxation over almost one decade in temperature and a direct comparison to the local model of strong pinning without introducing an additional time scale related to ageing [6,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation